Facial synthesis of dandelion-like g-C3N4/Ag with high performance of photocatalytic hydrogen production. (15th November 2019) - Li, Feihui; Zhao, Ruiru; Yang, Bingye; Wang, Wei; Liu, Yu; Gao, Jianping; Gong, Yunlan
Abstract: Nowadays, energy shortage is one of the major problems in the world. Photocatalytic hydrogen production is a new type of energy technology with good application prospect. As a new type of photocatalytic semiconductor material, g-C3 N4 has attracted much attention as a photocatalyst. By ultrasonic treatment of a mixed solution of g-C3 N4 and bovine serum albumin, followed by adding a certain amount of silver nitrate solution and then directly hydrothermal treatment, a special dandelion-like g-C3 N4 /Ag (D-g-C3 N4 /Ag) was prepared. The scanning electronic microscopy, transmission electronic microscopy, X-ray diffraction, Fourier transform infrared, fluorescence and physicochemical adsorption methods were used to characterize the morphology and structure of D-g-C3 N4 /Ag. In addition, the photocatalytic H2 production of D-g-C3 N4 /Ag with different Ag loadings or in different sacrificial agents and different pH conditions were investigated. The results indicated that when triethanolamine was used as sacrificial agent, photocatalytic hydrogen efficiency was the best, and the rate of photocatalytic hydrogen production reached 862 μmol g −1 h − 1 as the Ag loading was 4%. Graphical abstract: Dandelion-like g-C3 N4 /Ag with enhanced photocatalytic H2 production performance. Image 1 Highlights: Dandelion-like g-C3 N4 /Ag (D-g-C3 N4 /Ag) was prepared. Dandelion-like g-C3 N4 is composed of g-C3 N4 nanorods. D-g-C3 N4 /Ag shows enhanced photocatalytic hydrogen production performance.